Matriz para la selección de un fluido de perforación base agua, con el fin de prevenir el daño a la formación en el campo Castilla, Colombia (2019)
The present project, has the objective of design a selection matrix, through a theoretical methodology, which allows appraise the parameters or requirements necessary for formulation of water based drilling fluids, reducing the damage formation, cause by the obstruction of the porous medium. Taking into account the above, a preliminary diagnosis was made of the production formations present in the Castilla field, describing their main characteristics. Subsequently, a brief description of the properties, functions and types of drilling fluids, focusing on reservoir drilling fluids. Considering that one of the mechanisms that induces the formation damage, is the incompatibility between the drilling fluid and the fluids present in the reservoir, was evaluated the main factors that alter the physicochemical equilibrium of the crude oil and the formation water, generating organic and inorganic precipitates, that reduces the diameter of the pore throat. Finally, all the information collected is consolidated in a matrix in Excel format, that allows the user to selection the type and particle size of the additives that make up the drilling fluids, with the purpose to avoid incompatibilities, that generate solid deposits in the flow channels adjacent to the well.